Perlindungan Hukum Terhadap Konsumen Atas Peredaran Produk Kosmetik Ilegal Yang Mengandung Bahan Berbahaya (Studi Badan Pengawas Obat dan Makanan Medan) - Elfrida Mayang Sari HTP; Anggreni Atmei Lubis; Dessy Agustina Harahap (Universitas Medan Area, 2023)
Currently, there are many illegal cosmetics circulating in the market, whether they do not have a distribution permit or contain hazardous materials, including local and imported cosmetics. Therefore, it is necessary to have legal protection for consumers so that their rights are still fulfilled for the losses they experience. Cosmetic products are supervised by the Food and Drug Supervisory Agency or BPOM which is in charge of supervising the distribution of cosmetics as well as medicines and food in Indonesia. The research objectives to be achieved in this study are to find out how the law provides protection to consumers against the occurrence of illegal cosmetic circulation, to find out how the legal rules for the circulation of illegal cosmetics in Indonesia are, and to find out how legal remedies can be taken by the public for the circulation of illegal cosmetic products. . The research methods used are: Library Research and Field Research. Types of Normative Juridical Research. The conclusion obtained is that legal protection for consumers can be done by applying the principle of Strict Liability, namely mistakes are not a determining factor, but there are exceptions that allow business actors to be released from responsibility due to compelling circumstances. With the principle of absolute responsibility, it is hoped that business actors will prioritize the interests or rights of consumers, so that consumers do not experience losses for their actions or for cosmetic products produced or sold. The legal arrangements for the distribution of cosmetics in Indonesia include Law Number 8 of 1999 concerning Consumer Protection, Law Number 36 of 2009 concerning Health, BPOM Regulation Number 2 of 2020 concerning Supervision of Production and Distribution of Cosmetics, etc. Legal remedies that can be taken by the community are through the Court (Litigation) and BPSK (Non-Litigation).